Microwave Induced Synthesis of Alkyl-2-(2-alkoxy-2- (oxoethyl)dinaphtho[2,1-d:1,2-f][1,3]-dioxepin-2- carboxylates from Stabilized Phosphorus Ylides - RAMAZANI, ALI; MASSOUDI, Abdolhossain; Amini, Issa (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by 1,1-binaphthyl-2,2'-diol leads to vinyltriphenylphosphonium salts, which undergo Michael addition reaction with conjugate base to produce corresponding stabilized phosphorus ylides. Magnesium oxide powder was found to catalyze conversion of the stabilized phosphorus ylides to alkyl 2-(2-alkoxy-2-oxoethyl)dinaphtho[2,1-d:1,2-f][1,3]-dioxepin-2-carboxylates in solvent-free conditions under microwave (0.6 KW, 3 min) and thermal (100ºC, 1 h) conditions.